Predictors and pathways of language and motor development in four prospective cohorts of young children in Ghana, Malawi, and Burkina Faso - Prado EL (WILEY, 2022)
Background: Previous reviews have identified 44 risk factors for poor early child development (ECD) in low- and middle-income countries. Further understanding of their relative influence and pathways is needed to inform the design of interventions targeting ECD. Methods: We conducted path analyses of factors associated with 18-month language and motor development in four prospective cohorts of children who participated in trials conducted as part of the International Lipid-Based Nutrient Supplements (iLiNS) Project in Ghana (n = 1,023), Malawi (n = 675 and 1,385), and Burkina Faso (n = 1,122). In two cohorts, women were enrolled during pregnancy. In two cohorts, infants were enrolled at 6 or 9 months. In multiple linear regression and structural equationmodels (SEM), we examined 22 out of 44 factors identified in previous reviews, plus 12 additional factors expected to be associated with ECD. Results: Out of 42 indicators of the 34 factors examined, 6 were associated with 18-month language and/or motor development in 3 or 4 cohorts: child linear and ponderal growth, variety of play materials, activities with caregivers, dietary diversity, and child hemoglobin/iron status. Factors that were not associated with child development were indicators of maternal Hb/iron status, maternal illness and inflammation during pregnancy, maternal perceived stress and depression, exclusive breastfeeding during 6 months postpartum, and child diarrhea, fever, malaria, and acute respiratory infections. Associations between socioeconomic status and language development were consistently mediated to a greater extent by caregiving practices than by maternal or child biomedical conditions, while this pattern for motor development was not consistent across cohorts. Conclusions: Key elements of interventions to ensure quality ECD are likely to be promotion of caregiver activities with children, a variety of play materials, and a diverse diet, and prevention of faltering in linear and ponderal growth and improvement in child hemoglobin/iron status.